Uma análise da contribuição das redes sociais na internet para o comércio eletrônico: social-commerce - Ferrara, Gustavo Hildebrand (2013)
The social networking on the internet has contributed to changes in commerce, being increasingly used by companies, as a channel of direct communication with the target audience, enabling the appearance of so-called social-commerce. Thus, the social-commerce has provided an interesting solution for companies and individuals who built their business through e-commerce platforms, thus enabling the construction of a closer relationship between customers and companies. Large, medium, small companies, and especially microentrepreneurs, started to sell their products through these e-commerce platforms on social networks. These have the benefit of the appearance of applications that professionalized the company-client relationship. More and more popular, social networking platforms on the internet began to offer a number of features and applications that facilitated the management of online business, as well as promoting the dissemination of products, promotions, launches, the search for market information for both captation trend lines, as well as in the competition analysis. Also allowed market niches rather practically inexistent, to become profitable. Customers, in its turn, through social networks on the Internet have amplified their search capabilities, enabling the comparison of several similar products, prices, and find out about product characteristics, information through the experiences of other users in relation to products and services. This research was developed with the objective to analyze the contributions of social networks on the Internet for electronic commerce, resulting in businesses models called social-commerce. It was also sought in this research, to explore, describe and characterize the online business models, e-commerce, Amazon.com, the Internet social networking and social commerce. Finally, an analysis was done about how social networks on the Internet are characterized, influenced and allow the generation of a sales platform that has as main characteristic the e-loyalty, e-satisfaction and e-trust. For this purpose were used works of authors such as, Argenti, Goosen, Jenkins, Kotler, Osterwater, O'Reilly, Pisani and Piotet, Anderson, Qualman, Recuero, Slack, Santaella and Lemos, Cruz, among others who have studied electronic commerce and social networks. Were, also, used researches conducted by Nielsen, IBM, CETIC, IMF, IBOPE, SEBRAE, EBIT, US Departament of Commerce, among others, to obtain data confirming these contributions of social networks on the Internet as an efficient and effective platform to sell products, services, and also reach new market niches, new customers enabling micro, small, medium and large size businesses to emerge